Hubungan Stres Akibat Kerja dengan Perilaku Perawat dalam Menghadapi Keluarga Pasien di Ruang Anak-Anak RS. PKU Muhammadiyah Surakarta - Mustaqim, Nurullana Fitri; Tarwaka, PGDip, Sc, M. Erg, Tarwaka, PGDip, Sc, M. Erg; Sri Darnoto SKM, MPH, Sri Darnoto SKM, MPH (2016)
The stress of the nurses are feeling distress experienced by nurses in experienced the work caused by several factors, among others: the face of the patient's family. The purpose of this study was to determine the relationship of stress due to working with nurse's behavior in the face of the patient's family in the children's hospital. PKU Muhammadiyah Surakarta. This type of research is observational analytic with cross sectional approach. The research population was all nurses in the children's room totaling 30 nurses, divided into two rooms, namely space Mina 16 nurses and 14 nurse Trigger room at the hospital. PKU Muhammadiyah Surakarta. Gauges in the questionnaire using a questionnaire rating the Hamilton Anxiety Scale (HAM-A) with an alpha of 0.97 , The sampling technique using total sampling technique. The statistical test used in this study using Product Moment correlation test. The results of the study there was no significant relationship between work stress by nurses behavior in the face of the patient's family (p value = 0.131). It is recommended that nurses implement a healthy lifestyle, besides knowing the symptoms of stress as early as possible as a form of prevention of stress.